Parusnyj sport: Puti obespecenija raznostoronnosti podgotovki jachtsmenov - Tomilin, K. G. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The complex target programm of the training of the Russian Olympic Yachting team was developed by the author on the basis of results of his own researches, and on the generalized experience of foreign experts also. The author developed methods of the monitoring for complex science group and methodical maintenance of the training of Olympic team and students of institutes of physical culture on specialization "Yachting". The training devices used for perfection of special physical preparedness and technical skills are developed and offered by him.